Estimating and mapping the incidence of dengue and chikungunya in Honduras during 2015 using Geographic Information Systems (GIS) - Lysien I. Zambrano; Manuel Sierra; Bredy Lara; Iván Rodríguez-Núñez; Marco T. Medina; Carlos O. Lozada-Riascos; Alfonso J. Rodríguez-Morales (Elsevier, 2017)
Summary: Geographical information systems (GIS) use for development of epidemiological maps in dengue has been extensively used, however not in other emerging arboviral diseases, nor in Central America. Surveillance cases data (2015) were used to estimate annual incidence rates of dengue and chikungunya (cases/100,000 pop) to develop the first maps in the departments and municipalities of Honduras. The GIS software used was Kosmo Desktop 3.0RC1®. Four thematic maps were developed according departments, municipalities, diseases incidence rates. A total of 19,289 cases of dengue and 85,386 of chikungunya were reported (median, 726 cases/week for dengue and 1460 for chikungunya). Highest peaks were observed at weeks 25th and 27th, respectively. There was association between progression by weeks (p < 0.0001). The cumulated crude national rate was estimated in 224.9 cases/100,000 pop for dengue and 995.6 for chikungunya. The incidence rates ratio between chikungunya and dengue is 4.42 (ranging in municipalities from 0.0 up to 893.0 [San Vicente Centenario]). Burden of both arboviral diseases is concentrated in capital Central District (>37%, both). Use of GIS-based epidemiological maps allow to guide decisions-taking for prevention and control of diseases that still represents significant issues in the region and the country, but also in emerging conditions. Keywords: Dengue, Chikungunya, Arboviruses, Infectious diseases epidemiology, Honduras